The role of LGUs in the management of fisheries/aquatic resources some policy issues and proposal - Legaspi, Perla E. (Philippine Journal of Public Administration, 1997)
There are more than a few local government units (LGUs) depending in part or in whole, on their fisheries and aquatic resources as a source of livelihood and industry for the people. The Philippines is an archipelagic country with adequate marine resources, if manages competently and utilized efficiently and effectively by the concerned LGUs with the assistance of non-government organizations (NGOs). The implementation of the provisions of the Local Government Code of 1991 relating to fisheries/aquatic resource management has been documented in the six LGUs studied. Environmental management, conservation and protection must be high on the agenda of local chief executives especially now that the responsibility for such is already devolved to them.